Functional Characterization of the Cell Division Gene Cluster of the Wall-less Bacterium Mycoplasma genitalium - Martínez-Torró, Carlos; Torres-Puig, Sergi; Marcos-Silva, Marina; Huguet-Ramón, Marta; Muñoz-Navarro, Carmen; Lluch-Senar, Maria; Serrano, Luis; Querol, Enrique; Piñol, Jaume; Pich, Oscar Q. (Frontiers in Microbiology, 2021)
It is well-established that FtsZ drives peptidoglycan synthesis at the division site in walled bacteria. However, the function and conservation of FtsZ in wall-less prokaryotes such as mycoplasmas is less clear. In the genome-reduced bacterium Mycoplasma genitalium, the cell division gene cluster is limited to four genes: mraZ, mraW, MG_223 and ftsZ. In a previous study, we demonstrated that ftsZ was dispensable for growth of M. genitalium under laboratory culture conditions. Herein, we show that the entire cell division gene cluster of M. genitalium is non-essential for growth in vitro. Our analyses indicate that loss of the mraZ gene alone is more detrimental for growth of M. genitalium than deletion of ftsZ or the entire cell division gene cluster. Transcriptional analysis revealed a marked upregulation of ftsZ in the mraZ mutant. SILAC-based proteomics confirmed the overexpression of FtsZ in MraZ-deprived cells. Of note, we found that ftsZ expression was upregulated in non-adherent cells of M. genitalium, which arise spontaneously at relatively high rates. Single cell analysis using fluorescent markers showed that FtsZ localization varied throughout the cell cycle of M. genitalium in a coordinated manner with the chromosome and the terminal organelle. In addition, our results indicate a possible role for the RNA methyltransferase MraW in the regulation of FtsZ expression at the post-transcriptional level. Altogether, this study provides an extensive characterization of the cell division gene cluster of M. genitalium and demonstrates the existence of regulatory elements controlling FtsZ expression at the temporal and spatial level in mycoplasmas.